Non-Completely Displaced Traumatic Rib Fractures: Potentially Less Crucial for Pulmonary Adverse Outcomes, Regardless of Classification - Hongrye Kim; Su Young Yoon; Jonghee Han; Junepill Seok; Wu Seong Kang (Medicina)
Background and Objectives: Two major classification systems exist for rib fracture (RFX) displacement. One system uses a 50% displacement threshold: Grade I (<50%), Grade II (≥50% to <100%), and Grade III (completely dislocated). Another proposes a 10% threshold: Undisplaced (<10%), Offset (≥10% to <100%), and Displaced (completely dislocated). We analyzed risk factors for adverse outcomes for pulmonary complications and mortality according to both classification criteria. Materials and Methods: We retrospectively reviewed trauma registry and medical records from January 2019 to December 2023. All radiographic parameters were recorded based on initial computed tomography. Primary outcomes were pneumonia and other pulmonary complications requiring surgery. Least absolute shrinkage and selection operator (LASSO) regression was conducted to select risk factors and minimize overfitting. Multivariable logistic regression (MLR) was performed after LASSO. Results: Among the 621 patients, 61 (9.8%) had one or more adverse outcomes. In MLR, regardless of both classifications, the age (p < 0.001), ISS (p < 0.001), and number of completely displaced RFX (p = 0.001) were statistically significant. After excluding 280 patients with completely displaced RFX, we conducted a subgroup analysis with the remaining 341 patients. In this analysis, 22 (6.5%) patients experienced one or more adverse outcomes. Regardless of both classifications, the AIS head (p = 0.006), AIS extremities (p = 0.012), and number of segmental RFX (p < 0.001) were statistically significant in MLR. The area under the receiver operating curve for both MLR models was 0.757 in the total patient group and 0.823 in the subgroup that excluded patients with completely displaced RFX. Conclusions: Completely displaced RFX is the most crucial factor, regardless of the classification criteria. Unless ribs are completely displaced, the degree of displacement may not be crucial, and the number of segmental RFX was a significant risk factor.